Fondi Application To Enhance Students’ Speaking Learning: Students’ Views - Dinda Gustiana; Sholihatul Hamidah Daulay (Universitas Cokroaminoto Palopo, 2025)
This research aims to find out the students' perceptions of using the Fondi application in speaking practice. This research applied a descriptive qualitative approach with a case study method to understand students' perceptions after using the Fondi app. The subject of the study were 11th grade students at Bandung 1 Percut Sei Tuan Private High School, there were 30 participants, 28 female students and 2 male students. Data was collected through ten questionnaires and semi-structured interviews to five students to gain deeper insights into students' experiences using the Fondi application. After the data was collected, the researcher analyzed it using Thematic Analysis. The results show that students have a generally positive perception of the Fondi app, particularly in four keys aspects: accessibility, effectiveness, interactivity and flexibility. Students found Fondi easy to use, it is not difficult to log into Fondi even for beginners, being able to speak with native speakers without being face-to-face gives them more confidence. In addition, Fondi offers flexibility, allowing students to practice speaking at any time without time limit and also comes with some free features. Overall, this study concludes that the Fondi app is an effective tool in improving students' English speaking skills. The findings provide important implications for the development of interactive and flexible language learning applications.